Global Trends in Production Management and Operational Excellence: A Comprehensive Bibliometric Analysis (2024-2026) - Slamet Wibowo (Journal of Collaborative Industrial Management (JCIM), 2025)
This bibliometric study presents a systematic analysis of 200 peer-reviewed publications spanning 2024-2026, sourced from 41 leading international journals covering production management, manufacturing excellence, and operational optimization. The research encompasses articles published across diverse manufacturing sectors, integrating traditional lean methodologies with emerging Industry 4.0 technologies and sustainability imperatives. Using quantitative and co-occurrence analysis approaches, the study reveals critical publication trajectories, source quality metrics, and emerging research domains. The dataset demonstrates substantial scholarly engagement with mean total citations of 7.31 citations per article in 2024, declining to 1.32 in 2025 due to citation accumulation lag. The International Journal of Production Research emerges as the dominant publication outlet with 53 articles and h-index of 11, establishing itself as the primary dissemination channel for production optimization research. Geographic and institutional analysis reveals concentrated research contributions from advanced manufacturing centers and emerging economies simultaneously engaging with operational excellence paradigms. The findings establish that contemporary production management research increasingly integrates digital transformation, environmental sustainability, and supply chain resilience considerations alongside traditional efficiency optimization metrics. These insights provide scholars, practitioners, and journal editors with evidence-based understanding of the research landscape's evolution and critical publication venues for disseminating production management scholarship.